Characterization of Ba0.77Sr0.23TiO3 powder prepared from an oxalate co-precipitation and an impregnation method - Pusit Pookmanee (2018)
Barium titanate (BaTiO3) powder was prepared from an oxalate co-precipitation method with the starting precursors of barium chloride dihydrate and potassium titanium oxalate dihydrate with mole ratio of 1: 1. Precipitated powder was obtained after adding oxalic acid until the pH of the final solution was 2. The precipitated powder was milled and calcined at 700°C for 2 h. Sr-doped barium titanate (BaSrTiO3) powder was prepared by an impregnation method. Barium titanate calcined at 700 oC for 2 h was mixed with 2 and 4 mole % of Sr from strontium chloride hexahydrate. The mixed powder was calcined at 900°C for 2 h. The phase of Ba0.77Sr0.23TiO3 powder was studied by X-ray diffraction (XRD) and found to have a tetragonal structure after calcination at 900°C for 2 h. The morphology and chemical composition of Ba0.77Sr0.23TiO3 powder were investigated by a scanning electron microscope (SEM) and energy dispersive X-ray spectroscopy (EDS). The particle size of Ba0.77Sr0.23TiO3 powder was in the range of 0.2-0.3 μm with an irregular shape. The elemental composition of barium, strontium, titanium and oxygen showed the characteristic X-ray energy values.